The teaching ministry of the pulpit its history, theology, psychology and practice for today - Skinner, Craig (Grand Rapids, MI Baker, 1973)
Includes bibliographical references and indexes.
Copy one donated by S.John Bacon Publishing, Burwood, Victoria, September, 1973, and has letters concerning this donation to the college attached to inside back cover. Copy 2 donated by the author, August, 1976
Keywords: Preaching